Bone Mesenchymal Stem Cells Contribute to Ligament Regeneration and Graft–Bone Healing after Anterior Cruciate Ligament Reconstruction with Silk–Collagen Scaffold - Fanggang Bi; Yangdi Chen; Junqi Liu; Wenhao Hu; Ke Tian (Stem Cells International)
Anterior cruciate ligament (ACL) reconstruction was realized using a combination of bone mesenchymal stem cells (BMSCs) and silk–collagen scaffold, and an in vivo evaluation of this combination was performed. By combining type I collagen and degummed silk fibroin mesh, silk–collagen scaffolds were prepared to simulate ligament components. BMSCs isolated from bone marrow of rabbits were cultured for a homogenous population and seeded on the silk–collagen scaffold. In the scaffold and BMSC (S/C) group, scaffolds were seeded with BMSCs for 72 h and then rolled and used to replace the ACL in 20 rabbits. In the scaffold (S) group, scaffolds immersed only in culture medium for 72 h were used for ACL reconstruction. Specimens were collected at 4 and 16 weeks postoperatively to assess ligament regeneration and bone integration. HE and immunohistochemical staining (IHC) were performed to assess ligament regeneration in the knee cavity. To assess bone integration at the graft–bone interface, HE, Russell–Movat staining, micro-CT, and biomechanical tests were performed. After 4 weeks, vigorous cell proliferation was observed in the core part of the scaffold in the S/C group, and a quantity of fibroblast-like cells and extracellular matrix (ECM) was observed in the center part of the graft at 16 weeks after surgery. At 4 and 16 weeks postoperatively, the tenascin-C expression in the S/C group was considerably higher than that in the S group (4 w, p<0.01; 16 w, p<0.01). Furthermore, bone integration was better in the S/C group than in the S group, with histological observation of trabecular bone growth into the graft and more mineralized tissue formation detected by micro-CT (4 w, bone volume fraction (BV/TV), p=0.0169, bone mineral density (BMD), p=0.0001; 16 w, BV/TV, p=0.1233, BMD, p=0.0494). These results indicate that BMSCs promote ligament regeneration in the knee cavity and bone integration at the graft–bone interface. Silk–collagen scaffolds and BMSCs will likely be combined for clinical practice in the future.